2018
DOI: 10.3389/fimmu.2018.02537
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Smad7 Promotes Inflammation in Rheumatoid Arthritis

Abstract: Objective: Smad7 is an inhibitory Smad and plays a protective role in many inflammatory diseases. However, the roles of Smad7 in rheumatoid arthritis (RA) remain unexplored, which were investigated in this study.Methods: The activation of TGF-β/Smad signaling was examined in synovial tissues of patients with RA. The functional roles and mechanisms of Smad7 in RA were determined in a mouse model of collagen-induced arthritis (CIA) in Smad7 wild-type (WT) and knockout (KO) CD-1 mice, a strain resistant to autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…As clearly described in the paragraph describing TGF-β-mediated molecular pathways, TGF-β, through both type I and type II receptors, regulates TGF-β-responsive genes transcription by inducing the phosphorylation of Smad2 and Smad3 [ 76 , 80 , 146 ]. In addition, TGF-β induces Smad7 expression, which negatively regulates TGF-β/Smad signalling via a feedback inhibitory mechanism [ 92 ].…”
Section: Tgf-β-induced Emt: Molecular Mechanisms In Rheumatoid Artmentioning
confidence: 99%
See 2 more Smart Citations
“…As clearly described in the paragraph describing TGF-β-mediated molecular pathways, TGF-β, through both type I and type II receptors, regulates TGF-β-responsive genes transcription by inducing the phosphorylation of Smad2 and Smad3 [ 76 , 80 , 146 ]. In addition, TGF-β induces Smad7 expression, which negatively regulates TGF-β/Smad signalling via a feedback inhibitory mechanism [ 92 ].…”
Section: Tgf-β-induced Emt: Molecular Mechanisms In Rheumatoid Artmentioning
confidence: 99%
“…In addition, TGF-β induces Smad7 expression, which negatively regulates TGF-β/Smad signalling via a feedback inhibitory mechanism [ 92 ]. Based on these assumptions, in RA patients, the loss of inhibitory Smad7 was associated with a marked activation of TGFβ/Smad3 signalling and the development of arthritis [ 146 ]. Furthermore, in RA, not only did the inhibition of Smad7 promote TGFβ/Smad3 signalling and tissue fibrosis, but it also markedly enhanced NF-κB-driven inflammation [ 146 ].…”
Section: Tgf-β-induced Emt: Molecular Mechanisms In Rheumatoid Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies revealed that TGF-β could persuade Smad2/3 phosphorylation to promote fibroblast differentiation ( Huang et al., 2019 ). It was also reported that, smad7 is an inhibitory Smad and plays a protective role in several inflammatory disorders by down regulating the phospho- smad3 ( Zhou et al., 2018 ). These evidences impelled us to focus on the impact of BCA on TGF-β/Smad signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Xu et al found that abnormal activation of TGF-β causes articular subchondral bone destruction in the rheumatoid arthritis rat/ mouse models, and conditional deletion of TGF-βR2 in nestin-positive cells effectively halted progression of RA joint damage [37]. Zhou et al indicated that deletion of Smad7 promotes inflammation of rheumatoid arthritis [13]. Conversely, overexpression of Smad7 in the joint improves rheumatoid arthritis [38].…”
Section: Discussionmentioning
confidence: 99%